DESIGN OF TRANSMISSION LINE WITH USE OF PLS-CADD & MONITORING SAG AND TENSION - Kumar, Vipin; Kumar, Mantosh (International Journal of Engineering Technologies and Management Research, 2017)
Power is the basic key for growth of any country’s economy. The increased demand of electricity, need to optimize the utilization of power generation capacity and increase in the interconnections are the major issues with which power sector is dealing with. Energy consumption per person is also rising tremendously in developing countries. However, installing a new power plant cannot be a solution every time. Dense population, availability of land, initial and installation cost can be the major issues in this case. Huge transfer of power from generating plants to load centre at long distance with bulky transmission lines is causing to upgrade voltage class to Extra High Voltage (EHV) from High Voltage (HV). [1]